Viability of Multi-Specialty Dental Center in Bacolod City - Mendez, Jasmine Joyce G.; Mibato, Rizalie N.E. (Philippine Social Science Journal, 2020)
A Multi-Specialty Dental Center (MSDC) is one in which dentists share facilities, administration, income and expenses, support staff, and equipment. It is a single practice entity that provides general dentistry services in collaboration with the provision of one or more dental specialties. Moreover, dentists can specialize in related dental practices or offer a wide range of specialties. This business is relatively stable as it is a growing source of revenue. The primary purpose of a multi-specialty dental clinic is to serve all the needs of patients in one convenient location. Dental specialists can consult with each other and provide tests and radiological exams under one roof. Having a group of experts, dental professionals who can perform together to surpass a patient’s dental or aesthetic objectives is an advantage. It is also essential to address a potential challenge within the multi-specialty dental facility.